Epidemiology and outcomes of septic shock in children with complex chronic conditions in a developing country PICU - Leandra Rech; Ian Teixeira e Sousa; Cristian Tedesco Tonial; Jefferson Pedro Piva (Elsevier, 2022)
Objective: To investigate the role of Complex Chronic Conditions (CCCs) on the outcomes of pediatric patients with refractory septic shock, as well as the accuracy of PELOD-2 and Vasoactive Inotropic Score (VIS) to predict mortality in this specific population. Methods: This is a single-center, retrospective cohort study. All patients diagnosed with septic shock requiring vasoactive drugs admitted to a 13-bed PICU in southern Brazil, between January 2016 and July 2018, were included. Clinical and demographic characteristics, presence of CCCs and VIS, and PELOD-2 scores were accessed by reviewing electronic medical records. The main outcome was considered PICU mortality. Results: 218 patients with septic shock requiring vasoactive drugs were identified in the 30-month period and 72% of them had at least one CCC. Overall mortality was 22%. Comparing to patients without previous comorbidities, those with CCCs had a higher mortality (26.7% vs 9.8%; OR = 3.4 [1.3-8.4]) and longer hospital length of stay (29.3 vs 14.8; OR 2.39 [1.1- 5.3]). Among the subgroups of CCCs, "Malignancy" was particularly associated with mortality (OR = 2.3 [1.0-5.1]). VIS and PELOD-2 scores in 24 and 48 hours were associated with mortality and a PELOD-2 in 48 hours > 8 had the best performance in predicting mortality in patients with CCC (AUROC = 0.89). Conclusion: Patients with CCCs accounted for the majority of those admitted to the PICU with septic shock and related to poor outcomes. The high prevalence of hospitalizations, use of resources, and significant mortality determine that patients with CCCs should be considered a priority in the healthcare system.